2005
DOI: 10.1111/j.1468-1331.2004.00953.x
|View full text |Cite
|
Sign up to set email alerts
|

Fall‐related brain injuries and the risk of dementia in elderly people: a population‐based study

Abstract: Severe head injury in early adulthood may increase the risk of dementia in older age, but it is not known whether head injury in later life also increases the risk of dementia. A representative sample (82%) of persons aged 70 years or older with a Mini-Mental State Examination (MMSE) test score of > or =26 (n = 325) were followed-up for 9 years to record all their fall-related head injuries resulting in traumatic brain injury (TBI). At the end of the follow-up period, 152 persons (81% of the surviving populati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(30 citation statements)
references
References 57 publications
2
26
0
2
Order By: Relevance
“…Moreover, time since TBI, duration of loss of consciousness, multiple TBI and APOE-4 allele status did not influence the risk of dementia. Luukinen et al (2005) carried out a population-based study that included 325 individuals aged 70 years or older with an initial MMSE score greater than 27. During a 9-year follow-up period, eight individuals had a TBI and 34 individuals developed dementia.…”
Section: Prospective Studiesmentioning
confidence: 99%
“…Moreover, time since TBI, duration of loss of consciousness, multiple TBI and APOE-4 allele status did not influence the risk of dementia. Luukinen et al (2005) carried out a population-based study that included 325 individuals aged 70 years or older with an initial MMSE score greater than 27. During a 9-year follow-up period, eight individuals had a TBI and 34 individuals developed dementia.…”
Section: Prospective Studiesmentioning
confidence: 99%
“…Head injury in non-APOE ε4 carriers did not increase risk. Luukinen et al found fall-related TBI to predict earlier onset of dementia, particularly in APOE ε4 carriers [52], and Friedman et al found APOE ε4 carriers with TBI had significantly poorer functional outcome [53]. However, there are also many mixed findings with respect to the relationship between APOE genotype and TBI.…”
Section: Tbi and Apoe ε4 Allele: Increased Vulnerability For Dementiamentioning
confidence: 99%
“…(Table 12) There was some evidence suggesting an interaction between ApoE and head injury increases dementia risk. Two longitudinal cohort studies and one case-controlled study found that the two to five-fold increased risk of any dementia or AD associated with head injury that was traumatic, severe or of unspecified severity was only in individuals positive for the ApoE e4 allele (Luukinen et al, 2008(Luukinen et al, , 2005Sundstrom et al, 2007;Tang et al, 1996b). One crosssectional and one case-controlled study did not find a significant interaction, however examination of the odds ratios suggests a trend towards greater effect of head injury on dementia in persons positive for ApoE e4 (O'Meara et al, 1997b;Plassman et al, 2000).…”
Section: Dietmentioning
confidence: 98%